Transition Parameters for Doubly Ionized Lanthanum. (27th September 2012) - Karaçoban, Betül; Özdemir, Leyla
Abstract : The transition parameters such as the wavelengths, weighted oscillator strengths, and transition probabilities (or rates) for the nd ( n = 5 − 9 ) − nf   ( n = 4 − 8 ), nd ( n = 5 − 9 ) − np   ( n = 6 − 9 ), np ( n = 6 − 9 ) − ns   ( n = 6 − 10 ), and ng ( n = 5 − 8 ) − nf   ( n = 4 − 8 ) electric dipole ( E 1) transitions of doubly ionized lanthanum (La III, Z = 57 ) have been calculated using the relativistic Hartree-Fock (HFR) method. In this method, configuration interaction and relativistic effects have been included in the computations combined with a least squares fitting of the Hamiltonian eigenvalues to the observed energy levels. We have compared the results obtained from this work with the previously available calculations and experiments in literature. We have also reported new transitions with the weighted transition probabilities greater than or equal to 10 5 .